Metabolic, zootechnical, and health profile of Girolando calves conceived through in vitro fertilization - Maria Amélia Agnes Weiller; Evandro Schmoeller; Antônio Amaral Barbosa; Adriane Dalla Costa de Matos; Cassio Cassal Brauner; Marcio Nunes Corrêa; Francisco Augusto Burkert Del Pino; Viviane Rohrig Rabassa (Ciência Rural, 2024)
ABSTRACT: This study determined the zootechnical, metabolic, and health performance of Girolando calves born with high or low birth weight, conceived through in vitro fertilization. The study was carried out on a commercial dairy farm located in Passos, Minas Gerais, Brazil. For this, a hundred Girolando calves were divided into two groups: The Control, which consisted of calves that were born weighing ≤ 35 kg; and high birth weight (HBW) calves, which were born weighing > 35 kg. The calves were monitored for zootechnical parameters; epidemiological indices, for diseases such diarrhea and pneumonia; as well as serum concentrations of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, gamma-glutamyl transferase, cholesterol, triglycerides, paraoxonase1, albumin, urea, and globulin. Calves from the HBW group had a higher general mortality rate, but no effects on the zootechnical performance or metabolism were observed. The results obtained allow us to conclude that Girolando calves generated by IVF and heavier at birth have a greater chance to present diseases such as omphalophlebitis, tympany, and bovine parasitic sadness, and have a higher rate of general mortality. Conversely, birth weight of the calves does not influence diarrhea or pneumonia, the zootechnical performance, or the metabolism.